Anodized 20 nm diameter nanotubular titanium for improved bladder stent applications - Ece Alpaslan (Dove Medical Press, 2011)
Ece Alpaslan1, Batur Ercan2, Thomas J Webster2,31Faculty of Engineering and Natural Sciences, Sabanci University, Istanbul, Turkey; 2School of Engineering, 3Department of Orthopedics, Brown University, Providence, RI, USAAbstract: Materials currently used for bladder applications often suffer from incomplete coverage by urothelial cells (cells that line the interior of the bladder and ureter) which leads to the continuous exposure of the underlying materials aggravating an immune response. In particular, a ureteral (or sometimes called an ureteric or bladder) stent is a thin tube inserted into the ureter to prevent or treat obstruction of urine flow from the kidney. The main complications with ureteral stents are infection and blockage by encrustation, which can be avoided by promoting the formation of a monolayer of urothelial cells on the surface of the stent. Nanotechnology (or the use of nanomaterials) may aid in urothelialization of bladder stents since nanomaterials have been shown to have unique surface energetics to promote the adsorption of proteins important for urothelial cell adhesion and proliferation. Since many bladder stents are composed of titanium, this study investigated the attachment and spreading of human urothelial cells on different nanotextured titanium surfaces. An inexpensive and effective scaled up anodization process was used to create equally distributed nanotubular surfaces of different diameter sizes from 20–80 nm on titanium with lengths approximately 500 nm. Results showed that compared to untreated titanium stents and 80 nm diameter nanotubular titanium, 20 nm diameter nanotubular titanium stents enhanced human urothelial cell adhesion and growth up to 3 days in culture. In this manner, this study suggests that titanium anodized to possess nanotubular surface features should be further explored for bladder stent applications.Keywords: anodization, nanotube, urothelial cells, bladder applications, titanium